Kemampuan Membaca Pemahaman Siswa Sekolah Dasar Negeri 18 Anduring Kota Padang - Abdul Basit; Besral Besral; Mahmud Mahmud (Universitas Islam Negeri Imam Bonjol Padang, 2023)
The background of this research is that there are still many fifth grade students whose learning outcomes are low, especially in the learning aspect of reading comprehension. Fifth grade students still have difficulties in understanding reading texts. This study wanted to find out and analyze students' reading comprehension skills, reasons for difficulties and alternative solutions to overcome problems in reading comprehension in fifth grade students at SD Negeri 18 Anduring, Padang City. This research approach uses qualitative research subjects 8 students of class V SD. Data obtained through observation, interviews, tests, and documentation. The results of this study indicate that fifth grade students at SD Negeri 18 Anduring, Padang City have sufficient ability in literal comprehension skills and are classified as lacking in interpretive understanding, critical understanding, and creative understanding. Factors causing the difficulty of reading comprehension in fifth grade students of SD Negeri 18 Anduring, Padang City, namely interests and activities in pre-reading, reading, post-reading activities and differences in students' abilities, facilities and infrastructure and school environment and family upbringing. Solutions that can be implemented are changing students' habits to read books, providing facilities and infrastructure, and teachers can apply models, strategies and learning methods that are appropriate for students.